The issue of transshipment in border station with different gauges - Kurilov Ye.G. (Naučno-Tehničeskij Vestnik Brânskogo Gosudarstvennogo Universiteta, 2017)
This paper presents a comparison of technology delivery bulk cargo. The subject of study is the structure of the tech-nology delivery bulk cargo. The aim of the study is to improve the technological scheme of delivery of cargo in the supply chain. Methods based on the analysis and synthesis of existing methods of collecting baseline information, methods of processing it in a substantiation of the choice of the most efficient transportation technologies.